2017
DOI: 10.1021/jacs.6b11274
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of Coumarin and Carbostyril-Sensitized Luminescent Lanthanide Complexes: Implications for Complex Design in Multiplex Detection

Abstract: Luminescent lanthanide (Ln(III)) complexes with coumarin or carbostyril antennae were synthesized and their photophysical properties evaluated using steady-state and time-resolved UV-vis spectroscopy. Ligands bearing distant hydroxycoumarin-derived antennae attached through triazole linkers were modest sensitizers for Eu(III) and Tb(III), whereas ligands with 7-amidocarbostyrils directly linked to the coordination site could reach good quantum yields for multiple Ln(III), including the visible emitters Sm(III)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
126
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 112 publications
(185 reference statements)
8
126
0
1
Order By: Relevance
“…S11 †). The observed lifetimes and the intrinsic quantum yields are identical within experimental error within the group of Eu1a-d. Interestingly, in a previous study, an Eu complex with the same Ln binding site and a tertiary amide-linked 7-amidocoumarin antenna had a very similar observed lifetime, 0.65 ms, while a non-alkylated analogue had τ obs ∼ 0.6 ms. 39 Thus, N-alkylation indeed increases the Eu lifetime and the intrinsic quantum yield, probably because of the removal of the N-H oscillator.…”
Section: Absorption and Emission Spectroscopymentioning
confidence: 96%
See 4 more Smart Citations
“…S11 †). The observed lifetimes and the intrinsic quantum yields are identical within experimental error within the group of Eu1a-d. Interestingly, in a previous study, an Eu complex with the same Ln binding site and a tertiary amide-linked 7-amidocoumarin antenna had a very similar observed lifetime, 0.65 ms, while a non-alkylated analogue had τ obs ∼ 0.6 ms. 39 Thus, N-alkylation indeed increases the Eu lifetime and the intrinsic quantum yield, probably because of the removal of the N-H oscillator.…”
Section: Absorption and Emission Spectroscopymentioning
confidence: 96%
“…These conditions were chosen because previously we observed that Ln complexes with trifluoromethylated carbostyril antennae showed a reversible loss in Ln emission at pH > 7. 39 Analysis of the spectral shape of such Eu complexes showed no changes in the coordination environment, suggesting that deprotonation occurred in a non-coordinated group. As we could not exclude the loss of the core N-H proton, we have decided to do our experiments at a pH where deprotonation is not significant.…”
Section: Absorption and Emission Spectroscopymentioning
confidence: 97%
See 3 more Smart Citations